Adequacy of technical and vocational education and training at national diploma level, for employment in the clothing industry: the case of a Technical Teachers’ College in Harare. - Mutema, Katrah (2017)
The study sought to investigate the adequacy of Technical and Vocational Education and Training at National Diploma level, for employment in the clothing industry: The case of a Technical Teachers’ College in Harare. The quality and quantity of equipment found in training institutions triggered the researcher’s interest to carry out this research. A case study design was used to come up with answers to the research question. The population for the study was made up of thirty national diploma students who were pursuing Industrial Clothing Design and Construction course at a Technical Teachers’ College in Harare and who have also done On Job Training, seven Lectures from the clothing and Textiles section who taught modules from the Industrial Clothing Design and Construction course and ten production managers from clothing industries within Harare where the students were attached. Stratified and simple random sampling was used to select a sample from both students and production managers, while purposive sampling was used to select a sample from lecturers. The sample was made up of twelve students, six production managers and two lecturers to make a total of twenty participants. Questionnaires, interviews and observations were used to collect data from participants. The findings revealed that the training provided to national diploma students pursuing the Industrial Clothing Design and Construction course does not adequately equip them with appropriate skills to meet the needs of the clothing industry. It was also revealed that there is a wide gap between the type of equipment found in clothing industries and in the training institution which made it difficult for students to meet the needs of the clothing industry. The study recommends that Technical and Vocational Training Institutions seek donor funding in order to improve the quality and quantity of equipment in their workshops, heads of Technical and Vocational Training institutions to enrol students who can be accommodated by the available equipment, and that lecturers to go on Industrial attachment during vacation so that they learn how to use all the different industrial sewing machines so that they will improve their instructional methods for practical lessons.